2017
DOI: 10.1007/s00590-017-2023-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological results 7 years after Copeland shoulder resurfacing arthroplasty in patients with primary glenohumeral osteoarthritis: an independent multicentre retrospective study

Abstract: For primary osteoarthritis, the CSRA showed good clinical but poor radiological outcomes at midterm follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…3 Recent studies have reported mixed results of CRHA with 5-year survival estimated as low as 79% 4 and as high as 97.5%. 5,6 These studies included relatively small numbers of patients and used strict inclusion and exclusion criteria therefore may not be representative of the entire population.…”
Section: Introductionmentioning
confidence: 99%
“…3 Recent studies have reported mixed results of CRHA with 5-year survival estimated as low as 79% 4 and as high as 97.5%. 5,6 These studies included relatively small numbers of patients and used strict inclusion and exclusion criteria therefore may not be representative of the entire population.…”
Section: Introductionmentioning
confidence: 99%
“…Sweet et al 25 and Pritchett 31 reported 90% and 95% patient satisfaction with the procedure, respectively, compared to our 71.7% satisfaction with current symptoms, although definitions of satisfaction showing that despite poor radiographic outcomes at a mean of 7.2 years after HHR, clinical outcomes were good. 32 Our study has several limitations. First, patients were given the option of completing the PRO survey electronically or in paper form.…”
Section: Discussionmentioning
confidence: 91%
“…demonstrated a similar concept, showing that despite poor radiographic outcomes at a mean of 7.2 years after HHR, clinical outcomes were good. 32 …”
Section: Discussionmentioning
confidence: 99%
“…Especially, RHA has been promoted as a bone-sparing alternative to SHA for over ten years among doctors and patients. Various types of resurfacing procedures have been described in terms of shortand mid-term clinical effectiveness by mounting studies [32,53,[57][58][59][60] and a recent systemic review [61] suggested that resurfacing replacements could provide a significant improvement in pain, motion, and standardized outcome scores.…”
Section: Discussionmentioning
confidence: 99%
“…1b), which is a less invasive humeral head surface replacement with minimal bone resection. Subsequently, some studies reported that RHA could provide recovery of pain-free functional motion and facilitate the revision to TSA or RSA despite high complication rate during long-term follow-ups [30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%